PSYCHOLOGY OF EFFECTIVE COMMUNICATION IN ADVOCACY (Western European Journal of Historical Events and Social Science, 2026)
This article examines the psychological foundations of effective communication in legal practice and its role in ensuring professional success. In modern legal systems, the activity of a lawyer requires not only knowledge of legal norms but also advanced communicative competence and psychological culture. The study explores theoretical approaches to communication, including the cultural-historical theory of Lev Vygotsky, the activity theory of Alexey Leontiev, and the humanistic psychology of Carl Rogers. Special attention is given to verbal, paraverbal, and nonverbal communication, as well as emotional intelligence, empathy, and active listening as key factors of effective interaction. The article argues that the integration of psychological competence into legal practice enhances the quality of legal services, strengthens trust between lawyers and clients, and contributes to the administration of justice.